Adubação potássica e desenvolvimento de clones de eucalipto cultivados em Luís Eduardo Magalhães-BA - Sampaio, Thalita Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The Western Bahia region is one of the largest agricultural producers in Brazil, with approximately 2.3 million hectares (ha) cultivated mainly with crops of soybeans, corn and cotton, and Luís Eduardo Magalhães is one of the cities most prominent productive this region. Thus, there is growing interest from producers in cultivating eucalyptus due to increasing demand for wood by fertilizer companies, Beneficiadora grain and local producers for power generation as well as for civil and rural construction. However, there are still no clones of good adaptation set to region, as well as a calibrated fertilizer to obtain high productivity timber. It is known that developed through plant breeding is adapted to drought and regions with well-defined periods of drought clones, as is the case in the study area, and the management of K also affects this aspect, it regulates the opening and closing of the stomata, preventing the plant to lose water unnecessarily. Therefore, the aim of this study was to test the adaptation of eucalyptus clones and potassium levels for the conditions of western Bahia. The experimental design was a randomized block with four replications in a split plot design. The six clones (Cl) eucalyptus (AEC-056, AEC-144, AEC-220, AEC-224, AEC-103 and AEC-1528) and four doses of K2O (0, 30, 60 and 120 kg ha-1) were tested. The initial growth of the clones, the chemical characteristics of soil and plants and physiological characteristics of the plants were evaluated. Two years after planting Cl 1528 showed the largest growth and the lowest Cl 056. Chemical analysis of soil showed that the content of K in the soil reflected doses tested without influencing the growth of clones. The chemical analysis of the plants demonstrated that clones absorb different amounts of nutrients (N, Ca, Mg, S, B, Fe, and Zn) in the soil. Regarding physiological analyzes there was no effect of dose or tested clones

A região Oeste da Bahia é uma das maiores produtoras agrícolas do Brasil, com aproximadamente 2,3 milhões de hectares (ha) cultivados, principalmente com as culturas da soja, milho e algodão e Luís Eduardo Magalhães é uma das cidades de maior destaque produtivo. Com isso, é crescente o interesse dos produtores em cultivar eucalipto devido à crescente demanda de madeira pelas empresas de fertilizantes, beneficiadora de grãos e produtores locais para geração de energia, bem como para construção civil e rural. No entanto, ainda não existem clones de boa adaptação definidos para região, bem como uma adubação calibrada para obtenção de alta produtividade de madeira. Sabe-se que através do melhoramento genético obtem-se clones adaptáveis a regiões com déficit hídrico e épocas bem definidas de seca, como é o caso da região em estudo, e que o manejo do K também interfere neste aspecto, pois regula a abertura e o fechamento dos estômatos, impedindo que a planta perca água desnecessariamente. Logo, o objetivo deste trabalho foi testar a adaptação de clones de eucalipto e doses de potássio para as condições do local. O delineamento experimental foi em blocos ao acaso com quatro repetições, em esquema de parcelas subdivididas. Foram testados seis clones (Cl) de eucalipto (AEC-056, AEC-144, AEC-220, AEC-224, AEC-103 e AEC-1528), e quatro doses de K2O (0, 30, 60 e 120 kg ha-1). Foram avaliados o crescimento inicial dos clones, as características químicas de solo e plantas e características fisiológicas das plantas. Aos dois anos após o plantio o Cl 1528 foi o que apresentou maior crescimento e o Cl 056 o menor. A análise química de solo mostrou que o teor de K refletiu as doses testadas sem influenciar no crescimento dos clones. A análise química das plantas mostrou que os clones absorvem teores diferentes de nutrientes do solo. As doses ou clones testados ...
Keywords: Cerrados; Desidratação (Hídrica); Manejo florestal; Dehydration